Pembentukan Akhlaqul Karimah di Madrasah Aliyah Sumber Agung Kemiling Bandar Lampung - Subni, Subni (FKIP Universitas Lampung, 2017)
Abstract : Establishing of Akhlaqul Karimah in Madrasah Aliyah Sumber Agung Kemiling Bandar Lampung. This study aims to determine what factors are causing learners foul in school. Data obtained from this study is by observation, documentation and interview about the performance of teachers and learners. The field research is descriptive qualitative which is based on primary data, ie data obtained directly from the teacher aqidah akhlak and learners, and secondary data is data obtained indirectly, namely through media intermediaries or from other parties, such as principals and teachers’ board another. The data obtained is then analyzed inductively, by way of identifying things that are special and then pulled into general conclusions. Keyword: karimah akhlakul, madrasah aliyah, studentDOI: http://dx.doi.org/10.23960/jpp.v7.i2.201701